Immunity in kwashiorkor - Beatty, David William (Division of Immunology, 2017)
The adverse effects of malnutrition on the child are diverse and complex. This thesis describes an examination of the effects of severe malnutrition on immune defence mechanisms and in particular on cellular immune function in vitro.